Current trends and perspectives of bioactive peptides. Issue 13 (2nd September 2018) - Daliri, Eric Banan-Mwine; Lee, Byong H.; Oh, Deog H.
ABSTRACT: The remarkable growth of therapeutic peptide development in the past decade has led to a large number of market approvals and the market value is expected to hit 25 billion by 2018. This significant market increase is driven by the increasing incidences of metabolic and cardiovascular diseases and technological advancements in peptide synthesis. For this reason, the search for bioactive peptides has also increased exponentially. Many bioactive peptides from food and nonfood sources have shown positive health effects yet, obstacles such as the need to implement efficient and cost-effective strategies for industrial scale production, good manufacturing practices as well as well-designed clinical trials to provide robust evidence for supporting health claims continue to exist. Several other factors such as the possibility of allergenicity, toxicity and the stability of biological functions of the peptides during gastrointestinal digestion would need to be addressed.